The organization of industry - Stigler, George Joseph (Homewood, Ill. : R. D. Irwin, 1968)
The main content of this book is a reprinting of 17 articles written by the author over the past two decades in the area of industrial organization.
Includes bibliographies.
osc 04/12/2018
Loans
Keywords: Industrial organization (Economic theory); Industries; Antitrust law